2005
DOI: 10.1002/ijc.21008
|View full text |Cite
|
Sign up to set email alerts
|

Oral squamous cell carcinoma cells induce osteoclast differentiation by suppression of osteoprotegerin expression in osteoblasts

Abstract: The invasion of oral squamous cell carcinoma (SCC) cells into the mandibular bone is a common clinical problem. It has been reported that BHY cells, a human oral SCC cell line, are capable of invading mandibular bone of nude mice. These results led us to examine possible mechanisms of osteoclastogenesis induced by BHY cells using in vitro culture systems. When BHY cells were cocultured with mouse bone marrow cells (BMCs), only few osteoclasts were formed, even though BHY cells express the receptor activator of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 48 publications
5
48
0
1
Order By: Relevance
“…However, adding BHY cells to a coculture of mouse POBs and BMCs markedly induced osteoclastogenesis in the absence of osteotropic factors. Consistent with these results, HSC-2 cells, which do not express RANKL, also induced osteoclast formation in cocultures of mouse BMCs and POBs without any osteotropic factors (39). The addition of BHY cells suppressed mouse OPG mRNA expression and protein production by POBs.…”
Section: Rankl/rank Signaling Is Involved In Oral Scc Cell-induced Ossupporting
confidence: 77%
See 2 more Smart Citations
“…However, adding BHY cells to a coculture of mouse POBs and BMCs markedly induced osteoclastogenesis in the absence of osteotropic factors. Consistent with these results, HSC-2 cells, which do not express RANKL, also induced osteoclast formation in cocultures of mouse BMCs and POBs without any osteotropic factors (39). The addition of BHY cells suppressed mouse OPG mRNA expression and protein production by POBs.…”
Section: Rankl/rank Signaling Is Involved In Oral Scc Cell-induced Ossupporting
confidence: 77%
“…Several oral SCC cells in patients and oral SCC cell lines express RANKL (38)(39)(40). Recently, Chuang et al compared RANKL expression between buccal SCC without bone invasion (25 cases) and gingival SCC with invasion (15 cases).…”
Section: Rankl/rank Signaling Is Involved In Oral Scc Cell-induced Osmentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of bone-resorbing osteoclasts at the tumor-bone interface facilitates the osteolytic process and bone invasion of cancer cells (14). Recent studies indicated CXCR5 chemokine receptor expression by colon carcinoma cells and potential role in tumor growth (19).…”
Section: Discussionmentioning
confidence: 99%
“…Tumor cells activate bone resorbing osteoclasts, thereby facilitating the osteolytic process and bone invasion (14). RANKL is a critical osteoclastogenic factor in the bone microenvironment (7).…”
Section: Cxcl13 Stimulates Rankl Expression In Oscc Cellsmentioning
confidence: 99%